Effect of Kirinyuh Leaf Extract (Cromolaena odorata [L.] R.M. King & H. Rob) On Rice Paddy Growth (Oryza sativa L.) Variety of Mekongga in Drought Stress Condition - Wahyuni, Sarti; Lande, Martha L.; Zulkifli, Zulkifli; Handayani, Tundjung T. (Jurnal Penelitian Pertanian Terapan, 2018)
The purpose of this research was to know whether kirinyuh leaf water extract could improve the growth of mekongga varieties rice paddy under the condition of drought stress.This research was conducted at Botanical Laboratory of Biology Department Faculty of Mathematics and Natural Sciences University of Lampung from September to October 2017. The research was conducted in a 3 x 2 factorial experiment. Factor A was Polyethylene glicol 6000 with 3 levels of concentration: 0% w / v, 15% w / v, and 30% w / v. Factor B was kirinyuh leaf water extract with 2 concentration levels: 0% w / v and 2% w / v. As parameters were the mean of shoots length, fresh weight, dry weight, and the relative water content of rice seedling. Levene test, analysis of vaiance, and Tukey test were performed at 5% significant level. The results showed that water extract of kirinyuh leaves had no significant effect on shoot length, fresh weight, and dry weight of rice seedling, but influenced the relatife water content of rice seedling. From the result of research it was concluded that kirinyuh leaf water extract can not improve the growth of Mekongga rice paddy varieties at drougth stress condition